Effect of exposure inside the LHD vessel on reflectance of stainless steel mirrors - Voitsenya, V. S.; Sagara, A.; Bardamid, A. F.; Belyaeva, A. I.; Bondarenko, V. N.; Kudlenko, A. D.; Konovalov, V. G.; Solodovchenko, S. I. (National Science Center "Kharkiv Institute of Physics and Technology", 2002)
The efficiency of in-vessel mirrors of diagnostic systems of a fusion reactor will depend both on the mirror material and on the mirror location inside the reactor vacuum vessel. Till recently the data necessary to predict the behavior under a fusion reactor environment of mirrors fabricated of different metals with different structure were obtained in simulation experiments only. The first attempt to study the connection between the mirror location and modification of mirror optical properties was made two years ago for stainless steel mirror samples exposed inside the Large Helical Device (LHD) [2] during one experimental campaign. In this paper the main results obtained after investigation of samples taken out of LHD vessel are presented.
Keywords: in-vessel mirrors; fusion reactor; optical properties; boronization procedure; cleaning of mirrors